3(x-2)=3(x-2)+6

Simple and best practice solution for 3(x-2)=3(x-2)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)=3(x-2)+6 equation:


Simplifying
3(x + -2) = 3(x + -2) + 6

Reorder the terms:
3(-2 + x) = 3(x + -2) + 6
(-2 * 3 + x * 3) = 3(x + -2) + 6
(-6 + 3x) = 3(x + -2) + 6

Reorder the terms:
-6 + 3x = 3(-2 + x) + 6
-6 + 3x = (-2 * 3 + x * 3) + 6
-6 + 3x = (-6 + 3x) + 6

Reorder the terms:
-6 + 3x = -6 + 6 + 3x

Combine like terms: -6 + 6 = 0
-6 + 3x = 0 + 3x
-6 + 3x = 3x

Add '-3x' to each side of the equation.
-6 + 3x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + 0 = 3x + -3x
-6 = 3x + -3x

Combine like terms: 3x + -3x = 0
-6 = 0

Solving
-6 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7x^2-10xy+3y^2=0 | | 7x+13=5x+7 | | -(5x+1)=-7x+3 | | 15-x=-12 | | 9x^2-21xy-18y^2=0 | | .25w+4=-3(.25w+2)+8 | | -(6y+4)-(-5y-6)=-2 | | 8(5+4)= | | -3x+21=3x-21 | | x^4-10x^2-96=0 | | -50z-0.2=-60z+1.4 | | 8n-(3n+8)=32 | | -6y-1=5y-2 | | -[8x-(2x+7)]=1-(9x+3) | | 12+33=-5(2x-9) | | 3(7-x)-33=21x-4(3+6x) | | -8-(-n)=1 | | 8+24=-4(6x-8) | | -175=-29x-30 | | 2x^3-2x+9x^2-24x=0 | | 12x-3=24+5 | | 5x(4x+45)=360 | | -175=-29-30 | | 8n-(6n+7)=1 | | 2x^3-2x+9x^2-24=0 | | (t-1)(t+2)=0 | | 4(3x+9)=-31+7 | | 2/3-6h=13/6 | | -6x^2+15x=0 | | 10z-z=-3+2z-2-2 | | 33-12x=4x-97 | | 4.4x+55.9=16.3-8.8x |

Equations solver categories